Iceland : 2016 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Iceland. (IMF Staff Country Reports; Country Report ;, 2016)
This paper provides an assessment of the economic conditions, outlook, and crises in Iceland. There is a mounting sense that capital controls hurt growth prospects, repressing local financial markets, scaring foreign investors, and impeding savings diversification, and that it is time for them to go. Recent settlements with the bank estates are a huge step forward, improving already favorable macroeconomic conditions. At 4 percent in 2015 and gaining pace, real GDP expansion is among the fastest growing in Europe, opening up a positive output gap. However, the biggest risk for Iceland is overheating. Large wage awards on top of already hot economic readings speak to Iceland's boom-bust history.